Implementasi Turbin Listrik Mikrohidro sebagai Sumber Energi Listrik untuk Perkebunan Rakyat di Desa Gurah, Aceh Besar - Suriadi, Suriadi; Fathurrahman, Fathurrahman; Akram, Akram; Amir Azan, Said; Al Huda, Nafisah (Universitas Syiah Kuala, 2023)
The implementation of community service is one of the important tasks of tertiary institutions which requires educators to implement ideas that can directly benefit the community. This activity was carried out in accordance with the theme